Reliability and validity of Job Content Questionnaire for university research laboratory staff in Malaysia - Fadaei, Nehzat; Zainuddin, Huda; Syed Hassan, Syed Tajuddin (SEAMEO Regional Tropical Medicine and Public Health Network (SEAMEO TROPMED Network), 2014)
Job Content Questionnaire (JCQ) has been proven a reliable and valid instrument to assess job stress in many countries and among various occupations. In Malaysia, both English and Malay versions of the JCQ have been administered to automotive workers, schoolteachers, and office workers. This study assessed the reliability and validity of the instrument with research laboratory staff in a university. A cross sectional study was conducted among 258 research laboratory staff in Universiti Putra Malaysia (UPM). Malaysian laboratory staff who have worked for at least one year were randomly selected from nine faculties and institutes in the university that have research laboratory. A self-administered English and Malay version of Job Content Questionnaire (JCQ) was used. Three major scales of JCQ: decision latitude, psychological job demands, and social support were assessed. Cronbach's alpha coefficients of two scales were acceptable, decision latitude and psychological job demands (0.70 and 0.72, respectively), while Cronbach's alpha coefficient for social support (0.86) was good. Exploratory factor analysis showed five factors that correspond closely to the theoretical construct of the questionnaire. The results of this research suggest that the JCQ is reliable and valid for examining psychosocial work situations and job strain among research laboratory staff. Further studies should be done for confirmative results, and further evaluation is needed on the decision authority subscale for this occupation.